Detection Of Antibiotic Residues In Chicken Eggs At The Chicken Egg Farmers And Egg Distributors On Trading Business In Denpasar Municipality - Witoko, Maria Clafita; Suardana, I Wayan; Rudyanto, Mas Djok (Journal of Veterinary and Animal Sciences, 2019)
Antibiotic residues often found in food animal due to antibiotic usage for prevention and medication of diseases in livestock. The usage of antibiotics as growth promoter also often done by farmers to increase feed efficiency and enhance livestock’s growth, producing larger and heavier livestock that are more profitable. Food animal that contains antibiotic residues are neither safe nor qualified as human consumption. The objective of this research was to detect antibiotic residues in chicken eggs at chicken egg farmers and egg distributors in Denpasar, Bali. In order to determine antibiotic residues, a total of 24 chicken egg samples were randomly collected from farmers and distributors, followed by testing with bioassay method. The result showed that 13 out of 18 samples collected from farmers and 1 out of 6 samples collected from distributors were tested positive for antibiotic residues. Most of the tested positive samples contained aminoglycosides residue (66.7% on eggs collected from farmers), followed by tetracycline residue (44,4 on farmers egg and 16,7% on distributors egg) and macrolide residue (16,7% on farmers egg).